Implementasi Manajemen Risiko di SMK Al-Hasanain Beraim Praya Tengah - Hamdan; Ashabul Yamin (STIS DAFA MATARAM, 2023)
Risk management is a cause that often occurs in a company, organization, institution or other association which has an impact on losses, but if you try it well and seriously implement management, then all types of problems will be resolved quickly. In this research, data collection techniques were used, namely using Focus Group Discussion (FGD) or what is usually called discussion through observation, interviews and documentation. Al-Hasanain Beraim Vocational School implements school-based education management to develop and empower schools through various types of programs and empower human resources in order to improve school quality. Studies that are deepened through the implementation of risk management are related to human resources, achievements, causes experienced by schools, teachers and so on.